A "Pathology Explanation Clinic (PEC)" for Patient-Centered Laboratory Medicine Test Results. (19th March 2018) - Gibson, Blake; Bracamonte, Erika; Krupinski, Elizabeth A.; Briehl, Margaret M.; Barker, Gail P.; Weinstein, John B.; Weinstein, Ronald S.
This concept paper addresses communication issues arising between physicians and their patients. To facilitate the communication of essential diagnostic pathology information to patients, and address their questions and concerns, we propose that "Pathology Explanation Clinics" be created. The Pathology Explanation Clinics would provide a channel for direct communications between pathologists and patients. Pathologists would receive special training as "Certified Pathologist Navigators" in preparation for this role. The goal of Pathology Explanation Clinics would be to help fill gaps in communication of information contained in laboratory reports to patients, further explain its relevance, and improve patient understanding of the meaning of such information and its impact on their health and health-care choices. Effort would be made to ensure that Certified Pathologist Navigators work within the overall coordination of care by the health-care team.